The Improvement Strategy of Organizational Commitment through Strengthening Program of Organizational Climate, Self-Efficacy, and Job Satisfaction (An Empirical Study of Permanent Employees in the Multifinance Industry in Jakarta) - Joko Ariawan; Didik Notosudjonor; Widodo Sunaryo (Green Publisher, 2026)
Commitment to the organization is a strategic factor crucial for sustaining performance and employee retention, especially in the multifinance industry with its high work dynamics and operational demands. This study aims to analyze and develop strategies to enhance Organizational Commitment by strengthening program of Organizational Climate, Self-Efficacy, and Job Satisfaction among permanent staf-level employees. The population consists of 1,294 permanent employees in multifinance companies in Jakarta, with a sample of 248 selected through proportional random sampling. Employing a mixed-methods approach, the study combines quantitative analysis (indicator correlation and path analysis) with qualitative analysis (Delphi technique) to gather Human Resources expert input for formulating improvement strategies. Results reveal that Organizational Climate, Self-Efficacy, and Job Satisfaction have a direct, positive, and significant influence on Organizational Commitment. Additionally, Organizational Climate and Self-Efficacy indirectly influence Organizational Commitment through Job Satisfaction as a mediator. Findings emphasize strong superior support, increased employee confidence in self-competence, and promotion opportunities in job satisfaction aspects as key factors in strengthening commitment. This study provides strategic recommendations for Human Resources policy makers to design effective interventions in the multifinance industry.